The Effects of Folk Play Activities on Empathy of Early Childhood Children: The Effects of Folk Play Activities on Empathy of Early Childhood Children - Saardmuang, Dararat (RATANABUTH JOURNAL, 2023)
A study of the effects of folk play activities on the empathy aspect of preschool children. The objectives of this research were 1) to study the empathy of early childhood children. 2) to compare the empathy of preschool children and after organizing folk play activities The research hypothesis is that after organizing local play activities of early childhood children, have a higher development of empathy than before organizing folk play activities The sample group used in the research were Kindergarten 3 students in the second semester of the academic year 2022 at Ban Hua Ngua School. (Usupharaj Wittayakarn) under the Office of the Basic Education Commission, Kammaed Sub-district, Kut Chum District, Yasothon Province. There were 24 students in one classroom, obtained by purposive selection. There were 2 types of tools used in this study and data collection: 1) 20 plans activity of folk play activities on compassionate behaviors of early childhood children; another For kindergarten students, grade 3, 25 questions Summary of the study From the study and data analysis, the findings can be summarized as follows: 1. The development of empathy in early childhood children. that has been organized to play folk activities 2. Comparison of empathy development of preschool children. After organizing local play activities, early childhood children had high development in empathy. than before the event was statistically significant at the .05 level.